La traduction anglaise de Maria Stuarda : paradoxes et contradictions d’une reine catholique et puritaine - Pierre Degott (Revue LISA)
This article is about the only English singing-translation of Donizetti’s Maria Stuarda, as performed by the ENO in the 1970s and 80s. It aims at showing how the translated text considerably modifies the historical and political issues of the original version, the English text being a form of correction of the work of Schiller and Donizetti’s librettist, Giuseppe Bardari. If Donizetti’s work already offers, via Schiller, a somewhat revised version of History, the translation and recontextualisation of the opera pushes the transformation a little bit further. The paper thus examines some of the religious and historical aspects of such a cultural transfer, but also some of the musical modifications brought to the score. These were no doubt justified by the presence on the ENO stage of the mezzo-soprano Janet Baker, a national icon in the 1970s. Dame Janet’s assumption of this controversial role no doubt contributed to the general process of rewriting at the core of such an adaptation.